(3eSGFd hJeGQjf eMdhdIs - (3fhQj(B, (3MGTjs ((3GdLRGFQ(B:s (3GdfTQ GdLGeYj GdLOjO(B,s, 2021)
-(3eONd ddGMUGA GdhUaj,YQV GdHjGfGJ GdGMUGFjI ,eY CfhGY GdUaGJ Ch GdeJZjQGJ hGdLOGhd GdGMUGFjI eY GdJeKjd GdHjGfj,hebGjjS GdfRYI GdeQcRjI eY GdhSW Ch GdeJhSW GdMSGHj ,hGdeJhSW GdgfOSj ,hcPdc ebGjjS GdJTJJ hGdTcd ,HeG ajg GdeOi GdYGe hGdeOi GdQHjYj hGdGfMQGas
(3eQGLY U(B.325-327 (3edGMb U(B.329-334s
Keywords: (3GdGMJeGdGJ(B((3QjGVjGJ(B)s; (3GdGMUGA GdhUajs